2015
DOI: 10.4103/2277-9531.154120
|View full text |Cite
|
Sign up to set email alerts
|

The impact of education intervention on the Health Belief Model constructs regarding anxiety of nulliparous pregnant women

Abstract: Background:According to investigations, pregnant women hypothesized that anxiety is a common factor that will improve spontaneously; they are not aware of its side effects on the fetus, baby, and pregnancy outcome, as a whole. Other studies have also not tried to design a theoretical framework based on Health Education Models (HBMs) to overcome this problem. The current study aimed at exploring the effectiveness of education on the anxiety of nulliparous women based on a HBM.Materials and Methods:An experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 3 publications
4
10
0
1
Order By: Relevance
“…The mean score of self-efficacy showed a significant increase in the intervention group after the intervention, which is in line with the results of similar studies (Jackson, 1997;Kealey et al, 2009;Shahnazi, Sabooteh, Sharifirad, Mirkarimi, & Hassanzadeh, 2015;Tavassoli et al, 2015). Fostering the belief in the students that they can perform safe behaviors improves their chances of obeying traffic regulations (Farma et al, 2014;Hajian, Vakilian, Najabadi, Hosseini, & Mirzaei, 2011;Jackson, 1997;Nazari et al, 2008;Rosenstock & Stretcher, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…The mean score of self-efficacy showed a significant increase in the intervention group after the intervention, which is in line with the results of similar studies (Jackson, 1997;Kealey et al, 2009;Shahnazi, Sabooteh, Sharifirad, Mirkarimi, & Hassanzadeh, 2015;Tavassoli et al, 2015). Fostering the belief in the students that they can perform safe behaviors improves their chances of obeying traffic regulations (Farma et al, 2014;Hajian, Vakilian, Najabadi, Hosseini, & Mirzaei, 2011;Jackson, 1997;Nazari et al, 2008;Rosenstock & Stretcher, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…The present study result is also in the same line with some other recent studies Khoramabadi et al, 2016 and Shahnazi et al, 2015 [23,24] who studied the effect of education based on HBM on different health behaviors. They emphasized that changing the health belief is prerequisite for behavior change.…”
Section: Discussionsupporting
confidence: 82%
“…This result is similar to at least two studies Khoramabadi et al, 2016 and Shahnazi et al, 2015 [23,24]. They had studied the effects of education based HBM on different health behavior among pregnant women.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Previous reports have shown that a child whose mother has a lower education level is less likely to receive full immunizations [ 28 , 29 ]. Besides this, a mother with a higher education background would have a better awareness and capacity to take advantage of an immunization service [ 30 , 31 , 32 , 33 ]. Third, we assumed that mothers with jobs had less time to spare for childhood immunization as it might not be one of the priorities amidst other competing events to bring healthy children to obtain vaccinations.…”
Section: Discussionmentioning
confidence: 99%